Evaluation of invalid vaccine doses in 31 countries of the WHO African Region. Issue 7 (11th February 2015) - Akmatov, Manas K.; Kimani-Murage, Elizabeth; Pessler, Frank; Guzman, Carlos A.; Krause, Gérard; Kreienbrock, Lothar; Mikolajczyk, Rafael T.
Highlights: A systematic evaluation of invalid vaccinations has not been performed yet in countries of the WHO African Region. Invalid vaccinations are common in countries of the WHO African Region. Invalid vaccinations were partly associated with individual and with community associated factors. Community contextual factors should be considered when planning immunization services. Abstract: We examined (a) the fraction of and extent to which vaccinations were administered earlier than recommended (age-invalid) or with too short intervals between vaccine doses (interval-invalid) in countries of the World Health Organisation (WHO) African Region and (b) individual- and community-level factors associated with invalid vaccinations using multilevel techniques. Data from the Demographic and Health Surveys conducted in the last 10 years in 31 countries were used. Information about childhood vaccinations was based on vaccination records ( n = 134, 442). Invalid vaccinations (diphtheria, tetanus, pertussis [DTP1, DTP3] and measles-containing vaccine (MCV)) were defined using the WHO criteria. The median percentages of invalid DTP1, DTP3 and MCV vaccinations across all countries were 12.1% (interquartile range, 9.4–15.2%), 5.7% (5.0–7.6%), and 15.5% (10.0–18.1%), respectively. Of the invalid DTP1 vaccinations, 7.4% and 5.5% were administered at child's age of less than one and two weeks, respectively. In 12 countries, the proportion of invalid DTP3 vaccinations administered with an interval of less than two weeks before the preceding dose varied between 30% and 50%. In 13 countries, the proportion of MCV doses administered at child's age of less than six months varied between 20% and 45%. Community-level variables explained part of the variation in invalid vaccinations. Invalid vaccinations are common in African countries. Timing of childhood vaccinations should be improved to ensure an optimal protection against vaccine-preventable infections and to avoid unnecessary wastage in these economically deprived countries.